Meningkatkan Produktivitas Kerja Guru Agama Kristen di Indonesia - Jannes Eduard Sirait (SIKIP: Jurnal Pendidikan Agama Kristen, 2022)
The purpose of this study is to analyze the factors that affect the productivity of teachers in their performance. Christian religious teachers who lose their enthusiasm have an impact on the ups and downs of work productivity to the lowest level. Teacher work productivity includes values, namely increasing morale through hard work and smart work. The teacher does not only fulfill his duties as a teacher but includes the overall ownership of the desire to carry out tasks according to his skills. They can be mature and independent and communicate effectively with peers. This research is descriptive in nature so that the resulting collection of facts is descriptive. This method can describe the object under study in detail. The position researcher is the main informant. Research informants are parents of students, prospective Christian teachers, lecturers, and Christian leaders. The method used in collecting information through observation includes the use of Google Forms. Conducting special interviews with some of the people who are considered the most knowledgeable about teacher work productivity by telephone and WhatsApp. Data analysis was carried out according to the Miles concept. The conclusion of the study is that teacher work productivity is influenced by various factors such as needs, psychological, social, economic, skills, experience, age, talent, physical condition, education level, temperament, and others. The main factors that affect the productivity of the teacher's performance are teaching skills and abilities, attitudes and character, school environment and conditions, work motivation, welfare, education level, work agreements, and the ability to apply technological achievements. AbstrakTujuan penelitian ini adalah menganalisis anasir-anasir yang mempengaruhi produktivitas guru dalam kinerjanya. Guru agama Kristen yang kehilangan semangat berdampak terhadap naik turunnya produktivitas kerja hingga terjun ke level terendah. Produktivitas kerja guru mencakup nilai, yaitu meningkatkan moral melalui kerja keras dan kerja cerdas. Guru bukan hanya melakukan pemenuhan tugas sebagai pengajar tetapi mencakup keseluruhan kepemilikan hasrat melakukan tugas sesuai kecakapan. Mereka dapat dewasa serta mandiri dan berkomunikasi secara efektif bersama rekan sejawat. Riset ini bersifat deskriptif sehingga kumpulan fakta yang dihasilkan adalah deskriptif. Metode ini mampu menggambarkan objek yang diteliti dengan detail. Kedudukan periset merupakan informan utama. Informan riset adalah orang tua siswa, calon guru agama Kristen, dosen, dan tokoh-tokoh Kristen. Cara yang digunakan dalam mengumpulkan informasi melalui pengamatan termasuk pemanfaatan Google Forms. Melakukan interviu secara khusus kepada beberapa orang yang dianggap paling mengerti tentang produktivitas kerja guru lewat telepon dan WhatsApp. Analisis data dilakukan menurut konsep Miles. Kesimpulan penelitian adalah produktivitas kerja guru dipengaruhi oleh berbagai faktor seperti kebutuhan, psikologis, sosial, ekonomi, keterampilan, pengalaman, usia, bakat, kondisi fisik, tingkat pendidikan, temperamen dan lain-lain. Anasir-anasir utama yang mempengaruhi produktivitas kinerja guru tersebut adalah kecakapan dan kemampuan mengajar yang dimiliki, sikap dan karakter, lingkungan dan kondisi sekolah, motivasi kerja, kesejahteraan, tingkat pendidikan, perjanjian kerja dan kemampuan menerapkan capaian teknologi.